Stretching has no effect on tennis serve performance - Knudson, D. V.; Noffal, G. J.; Bahamonde, R. E.; Bauer, J. A.; Blackwell, J. R. (The Journal of Strength and Conditioning Research, 2004)
Stretching prior to vigorous physical activity has been shown to decrease high-force muscular performance, but little is known about the effect of stretching on speed and accuracy movements. Serving percentage and radar measurements of ball speed were studied to examine the acute effect of stretching on tennis serve performance. Eighty-three tennis players from beginning level to advanced volunteered to serve following traditional (T) warm-up and traditional plus stretching (S) conditions. Service speeds and service percentage of each condition were measured. Dependent t-tests showed nonsignificant effects of stretching on service speed (p = 0.06) or accuracy (p = 0.35), and this lack of an effect was similar for all skill levels, age, and gender. The large sample and good statistical power in this study indicated that these observations are not likely type II errors. There was no short-term effect of stretching in the warm-up on the tennis serve performance of adult players, so adding stretching to the traditional 5-minute warm-up in tennis does not affect serve performance.